Development and Validation of Ultrahigh-Performance Liquid Chromatography Coupled with Triple Quadrupole Mass Spectrometry Method for Quantitative Determination of Ten Active Compounds in Ge-Gen-Jiao-Tai-Wan - Wenbo Wang; Shuangquan Zhu; Hao Chen; Ning Wu; Han Chen; Dongsheng Wang (Journal of Analytical Methods in Chemistry)
A rapid, accurate, and sensitive method for the simultaneous determination of 10 main components, namely puerarin, daidzin, coptisine, epiberberine, jatrorrhizine, berberine, palmatine, coumarin, daidzein, and cinnamic acid in Ge-Gen-Jiao-Tai-Wan, was developed based on ultra-high-performance liquid chromatography coupled with triple quadrupole mass spectrometry. Analysis was performed on an Agilent 1290 Infinity II series UHPLC system, equipped with a Waters ACQUITY UPLC HSS T3 column (100 × 2.1 mm, 1.8 μm) by using (A) 0.1% acetic acid and (B) methanol as mobile phase. The flow rate was 0.3 mL/min, and the injection volume was 1 μL. Mass spectrometry was operated in multiple reaction monitoring mode using an Agilent 6460 triple quadrupole mass spectrometer equipped with an AJS-ESI ion source. Agilent Mass Hunter Work Station Software was employed for data acquisition and processing. All calibration curves showed excellent linear regressions (R2 > 0.9992). The precision, repeatability, and stability of the ten compounds were below 4.56% in terms of relative standard deviation. The average extraction recovery ranged from 96.53% to 102.69% with a relative standard deviation of 1.14–3.78% for all samples. This study potently contributes to the quantitative evaluation of Ge-Gen-Jiao-Tai-Wan, thereby providing a scientific basis for further studies and clinical application of Ge-Gen-Jiao-Tai-Wan.